The Relationship between Smoking and the Incidence of Hypertension in Kebun Lada Public Health Center, Binjai, Indonesia - Jessica Patricia Laurent; Andrico Napolin Lumban Tobing; Andre Budi (HM Publisher, 2023)
Hypertension is a cardiovascular disease characterized by an increase in blood pressure. An increase in blood pressure causes a disruption in the distribution of blood to the target organs. The nicotine content in tobacco is believed to play a role in triggering a series of oxidative stress processes in the body. Oxidative stress plays a role in triggering a series of chronic inflammatory processes in the smoker's body. This study aimed to determine the relationship between smoking and the incidence of hypertension in patients at Kebun Lada Public Health Center, Binjai, Indonesia. Cross-sectional analytic observational study. A total of 75 research subjects participated in this study. Data analysis was carried out using SPSS using univariate and bivariate methods to determine the relationship between smoking and the incidence of hypertension. Subjects with normal blood pressure have a habit of not smoking. Meanwhile, the majority of research subjects with smoking habits experienced stage 1 hypertension. In conclusion, there is a relationship between smoking habits and the incidence of hypertension.